Penerapan Prosedur Audit Atas Piutang Usaha di Kantor Akuntan Publik Djoko, Sidik, Indra, dan Rekan (KAP DSI) - Muhammad Syauqi; Rizdina Azmiyanti (Fakultas Ekonomi Program Studi Akuntansi Universitas 45 Surabaya, 2024)
This research aims to find out a general description of the receivables audit procedures at KAP DSI starting from the planning stage, inspection stage and audit reporting stage carried out by KAP DSI. The main problem that is the focus of this research is knowing how audit procedures are carried out by a public accounting firm, especially in the accounts receivable section. The data collection strategy used included secondary data collection through library study techniques and participant-observational studies. The method used in this research was descriptive-qualitative. It is hoped that the results of this research can increase understanding regarding the implementation of the accounts receivable audit process at the Djoko, Sidik and Indra Public Accounting Firm.